CREDIT DISTRIBUTION: NON PERFORMING LOAN AND BI RATE, MEDIATED LOAN TO DEPOSIT RATIO (LDR) - Deden Edwar Yokeu Bernardin; Neng Diana Fitaloka (Jurnal Financia : Akuntansi dan Keuangan, 2022)
Banking as a medium of financial intermediation plays a role in supporting the growth of the national economy by channeling funds to the real sector in society. However, after the Covid-19 pandemic in Indonesia, the level of lending declined even though Bank Indonesia had lowered the BI Rate. The purpose of this study was to determine the magnitude of the effect of bad loans (NPL) and BI Rate on LDR and their impact on lending partially or simultaneously at PT Bank Mandiri (Perseo) Tbk. The population in this study is the financial statements of Bank Mandiri and the BI Rate statistical data, the sample in this study is the financial statements of Bank Mandiri and the BI Rate for the period 2011-2020, using purposive sampling technique for data collection techniques. The statistical method used is path analysis using the SPSS version 25 application. The results show that partially NPL and BI Rate have no significant effect on LDR, LDR has a significant effect on lending, bad loans (NPL) have no significant effect on lending, the BI Rate has no significant effect on lending, LDR is able to mediate the effect of the relationship between NPL and BI Rate on lending but with insignificant results. Simultaneously NPL, BI Rate and LDR have a significant effect on lending.